Overview of the IFMIF/EVEDA projectaIn Memoriam Yoshikazu Okumura who passed away on 6 March 2017. (30th June 2017) - Knaster, J.; Garin, P.; Matsumoto, H.; Okumura, Y.; Sugimoto, M.; Arbeiter, F.; Cara, P.; Chel, S.; Facco, A.; Favuzza, P.; Furukawa, T.; Heidinger, R.; et al.
Abstract: IFMIF, the International Fusion Materials Irradiation Facility, is presently in its engineering validation and engineering design activities (EVEDA) phase under the Broader Approach Agreement. The engineering design activity (EDA) phase was successfully accomplished within the allocated time. The engineering validation activity (EVA) phase has focused on validating the Accelerator Facility (AF), the Target Facility and the Test Facility (TF) by constructing prototypes. The ELTL at JAEA, Oarai successfully demonstrated the long-term stability of a Li flow under the IFMIF's nominal operational conditions keeping the specified free-surface fluctuations below ±1 mm in a continuous manner for 25 d. A full-scale prototype of the high flux test module (HFTM) was successfully tested in the HELOKA loop (KIT, Karlsruhe), where it was demonstrated that the irradiation temperature can be set individually and kept uniform. LIPAc, designed and constructed in European labs under the coordination of F4E, presently under installation and commissioning in the Rokkasho Fusion Institute, aims at validating the concept of IFMIF accelerators with a D + beam of 125 mA continuous wave (CW) and 9 MeV. The commissioning phases of the H + /D + beams at 100 keV are progressing and should be concluded in 2017; in turn, the commissioning of the 5 MeV beam is due to start during 2017. The D + beam through the superconducting cavities is expected to be achieved within the Broader Approach Agreement time frame with the superconducting cryomodule being assembled in Rokkasho. The realisation of a fusion-relevant neutron source is a necessary step for the successful development of fusion. The ongoing success of the IFMIF/EVEDA involves ruling out concerns about potential technical showstoppers which were raised in the past. Thus, a situation has emerged where soon steps towards constructing a Li(d, xn) fusion-relevant neutron source could be taken, which is also justified in the light of costs which are marginal to those of a fusion plant.